Preliminary Studies of a Propellant System for the Counterprojectile of an Active Protection System - Zbigniew SURMA; Mirosław ZAHOR; Przemysław KUPIDURA; Zbigniew Leciejewski (Problemy Mechatroniki)
This paper presents a selection of the deliverables for a research project intended to develop a technology demonstrator for a smart counterprojectile forming part of an active protection system. Given the required activation of the active protection system within a distance of ten or so metres from the protected facility, a solid-propellant rocket engine was used, which has the characteristics of a booster rocket. For the determined configuration of the rocket engine, the elements of the counterprojectile and missile launcher were designed, based on homogeneous rocket propellant of Polish origin. To confirm the validity of the adopted concept for the propulsion system solution, preliminary testing of the rocket engine was conducted using an engine test bed, and included the measurement of gas pressure and engine thrust for different masses of ignition charge. To ultimately verify the operation of the design, field testing of the counterprojectile propulsion system was carried out, based on which the parameters of projectile motion inside the missile launcher and along the initial flight path length were determined.